Yungay, the new Ayacucho: Commemorative rituals and the Gamarrist refoundation of Peru, 1839–1841 - Forsyth Tessey, Michael (2025)
Between 1839 and 1841, threatened by external enemies such as the governments of Bolivia and Ecuador, and internal ones, such as the elites of southern Peru, the second government of Agustín Gamarra sought to lay the foundations of the country for the following decades through complete political reform. This article explores the role that civic and commemorative rituals had in the construction of the legitimacy of the Gamarrista government, and the history of the commemoration ritual of the battle of Yungay, which was placed at the center of the republican calendar. For this purpose, primary sources such as the newspapers La Aurora Peruana, El Amigo del Pueblo and El Peruano, the Guía de forasteros, the Gamarra epistolary and the Colección de leyes, decretos y órdenes publicadas en el Perú, have been used.